A mathematical expression for tiemonium methylsulphate in its simultaneous spectrophotometric estimation with ketorolac tromethamine - Uddin, Mohammad Nasir; Kabir, Md. Touhidul; Uddin, Monir (European Journal of Chemistry, 2018)
Attempt has been made to develop a new, accurate, precise and economic spectrophotometric method for the simultaneous determination of ketorolactromethamine (KTR) and tiemoniummethylsulphate (TMS) in pharmaceutical formulation and bio-samples. It is noted that KTR shows two absorption peaks at 320 and 245 nm whereas TMS shows maximum absorption at 235 nm. In a mixture solution, peaks at 245 nm for KTR and at 235 nm for TMS are merged into a single peak at 240 nm. Hence KTR might be determined using its calibration equation constructed at 320 nm but the determination of TMS alone in their mixture measuring its absorption at 240 nm is difficult. Therefore, for the determination of TMS, a mathematical expression xT = k1.yK+T - k2.yK + k3 (y = Absorbance, x = Concentration) has been derived. This expression will give its concentration in mixture without having its absorption at 240 nm. Method has been applied to pharmaceutical and bio-samples successfully. Results have been compared to that estimated by new UPLC method developed as to validate this spectrophotometric method. The LOD and LOQ were found to be 0.25, 0.80 μg/mL for KTR and 0.31, 0.95 μg/mL for TMS, respectively.